Experimental investigation of recycled HDPE waste fiber-reinforced gypsum with emphasis on durability and mechanical performance - Warun Na Songkhla; Chalermphol Chaikaew; Burachat Chatveera; Gritsada Sua-iam (Results in Engineering)
The increasing demand for sustainable and durable construction materials has prompted interest in utilizing recycled waste in high-performance building composites. This study investigates the engineering and durability properties of gypsum-based composites reinforced with recycled high-density polyethylene (HDPE) fibers, at concentrations of 0 %, 0.5 %, 1.0 %, 1.5 %, and 2.0 % by gypsum volume. The experiments evaluated workability, compressive strength, sulfate resistance (via immersion in Na₂SO₄ and MgSO₄ for up to 90 days), and thermal performance at temperatures ranging from 50 °C to 200 °C. The results demonstrate that incorporating HDPE fibers significantly enhances strain capacity, especially under sulfate exposure. The mix with 2.0 % fiber content showed the greatest expansion, reaching 4.45 % in Na₂SO₄ and 4.8 % in MgSO₄ after 90 days, with expansion stabilizing after 30 days. This suggests that the gypsum binder’s high calcium oxide (CaO, 33.80 %) and sulfur trioxide (SO3, 50.14 %) contribute to improved chemical resistance. In terms of thermal performance, the fiber-reinforced composites retained 80–95 % of their compressive strength at 100 °C, outperforming those without fibers. These findings highlight the dual benefits of HDPE fibers: enhancing chemical resistance and thermal stability. The fibers improve deformability under sulfate attack and help preserve strength at elevated temperatures. This study offers an eco-friendly solution by integrating industrial waste into composites for applications requiring durability, thermal resilience, and environmental responsibility. Although the reduction in embodied carbon from incorporating HDPE is modest, it also contributes to reducing CO₂ emissions and aligns with the goals of a circular economy.